2014
DOI: 10.1093/abbs/gmu043
|View full text |Cite
|
Sign up to set email alerts
|

MiR-15a/b promote adipogenesis in porcine pre-adipocyte via repressing FoxO1

Abstract: Diabetes and many other metabolism syndromes are closely related to obesity. To reveal the underlying mechanism of fat deposition, an increasing number of studies are focusing on the functions of miRNAs during adipocytes development. Previous studies have proved that miR-15a/b play important roles in multiple physiological processes; however, their functions during adipogenesis remain unclear. To reveal this, we detected the expression profiles of miR-15a/b during adipogenesis in porcine pre-adipocyte, and fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 32 publications
3
40
2
Order By: Relevance
“…For example, the early muscle tissue of Duchenne muscular dystrophy is manifested as muscle ber regeneration and mild lipid droplets, and the late muscle bers are gradually replaced by fat and connective tissue, which seriously affects muscle function. Studies have pointed out that miR-15/16 promotes adipogenesis by targeting FOXO1 and EPT1 genes (28,29). In our results, the overexpression of circINSR in preadipocytes inhibited the expression of key genes for adipogenic differentiation and reduced lipid droplet formation.…”
Section: Discussionsupporting
confidence: 61%
“…For example, the early muscle tissue of Duchenne muscular dystrophy is manifested as muscle ber regeneration and mild lipid droplets, and the late muscle bers are gradually replaced by fat and connective tissue, which seriously affects muscle function. Studies have pointed out that miR-15/16 promotes adipogenesis by targeting FOXO1 and EPT1 genes (28,29). In our results, the overexpression of circINSR in preadipocytes inhibited the expression of key genes for adipogenic differentiation and reduced lipid droplet formation.…”
Section: Discussionsupporting
confidence: 61%
“…Targetscan.org suggested that miR15a could directly bind to the 3′UTR of Foxo1. Dong et al (2014) found that over-expression of miR15a/b interacted with the target region of Foxo1 mRNA in porcine pre-adi-pocytes (Dong et al, 2014). Using a luciferase assay, we confirmed that miR15a directly binds Foxo1 in REC.…”
Section: Discussionmentioning
confidence: 99%
“…Through the regulation of DLK1 level, miR-15a could disrupt adipogenic differentiation [ 12 ]. miR-15a can also target Foxo1, and participate in the disruption of adipogenic differentiation and the regulation of insulin synthesis [ 63 65 ]. miR-22 can regulate the PTEN/AKT pathway and target HDAC6 [ 66 68 ]; miR-206 and miR-1a can suppress hepatic lipogenesis [ 69 ]; miR-29b and miR-9 are involved in insulin sensitivity and diabetes [ 70 , 71 ]; miR-31 and miR-32 participate in differentiation of stem cells into adipocyte and lipid metabolism in oligodendrocytes [ 72 , 73 ].…”
Section: Discussionmentioning
confidence: 99%